Diferenças de gênero na resolução de dilemas morais : um estudo transcultural - Ponzoni, Aline (2021)
Morality is an essential element of the human being, who, on many occasions, needs to face complex decisions. Moral judgment is one of their central concepts, wich means the evaluative judgments that an observer makes in response to a moral violation. Moral dilemmas techniques are considered a standard methodology in moral judgment, as they make it possible to investigate the reasons and characteristics that influence moral decision-making. Moral dilemmas are characterized by fictional stories that describe a situation with two conflicting alternatives for resolution, based on deontological and utilitarian philosophical traditions. Based on them, some instruments have been developed. Recent literature has found gender-related differences in solving moral dilemmas. In addition, sociocultural factors seems to be important to properly understand morality, although there are aspects considered as universal. Thus, this dissertation aimed to investigate the moral dilemmas, about assessment instruments and the differences in gender and culture between countries; it consists of two studies: a theoretical and an empirical study. The theoretical study aimed to investigate moral dilemmas instruments used between 2010 and 2020 to assess moral judgment. For this, a systematic review of literature was carried out, analyzing 354 articles obtained from the Pubmed, PsycInfo, Scopus, and Web of Science databases. Eight studies were selected. The instruments found were: Moral Competence Test (MCT), Moral Judgment Test (MJT), Moral Sense Test (MST), Moral Thinking and Communication (MTC), and Moral Judgments of Sports Managers Instrument (MJSMI); the predominant use was not of assessment instruments, but of sets of dilemmas adapted to each research objective. The empirical study aimed to examine gender differences across culture in acceptability and emotional states in solving deontological and utilitarian dilemmas comparing Brazil and Spain. The sample consisted of young adults, with 333 participants from Brazil (46.2% men and 53.8 % women) and 292 from Spain (45.5 % men and 54.5 % women). They read and judged five moral dilemmas, answering a self-report scale, about acceptability, guilt, responsibility, consequences and emotional states. The main results are: i) the Spanish subsample appears to be more prone to accept moral transgressions, ii) differences between gender and country were found but without interactions across these two variables, iii) gender predicted acceptability exclusively for one of the utilitarian dilemmas. These findings suggest that morality has universal aspects that does not interact with gender. The dissertation contributions were: identify the most used assessment instruments; found gender differences in resolving moral dilemmas; suggest that morality has universal aspects; and highlight the importance of more cross-cultural studies to understand the influence of context on the moral values development.